Latinas/os in the United States
XXXVI, 392 p.
Keywords: Latinas/os in the United States: Changing the Face of América Edited by Rodríguez, Sáenz & Ménjivar The Latina/o population in the United States has experienced significant and rapid growth during the past decades. Consequently, they have become the largest minority group in the nation. Latinas/os are a mosaic of people, representing different nationalities. They are Mexicans, Hondurans, Puerto Ricans, Argentineans, Cubans, Salvadorans, Dominicans, Panamanians, Guatemalans, Nicaraguans, Peruvians, and Costa Ricans, among others; they are Catholics, Protestants, Jews, and Muslims, but they are also atheists, Santeros/as, and Curanderos/as. Many have relatively high and increasing levels of education, but others have low educational attainment and elevated high school attrition rates. They also have experienced significant economic mobility, yet many others are poor and face multiple forms of inequality. Latinas/os in the United States: Changing the Face of América explores and expands on these and other critical topics. This book also addresses important theoretical and methodological issues related to the study of Latinas/os and presents in-depth analyses (both quantitative and qualitative) of substantive issues relevant to this population, including migration, demographic patterns and processes, education, health, citizenship, political participation, religion, gender and sex roles, literary and cultural production, and the media. The authors seek to educate and increase awareness of the diversity that exists among the Latina/o population, and to carefully examine the social, economic, demographic, cultural, and political impacts and contributions that this growing population has had in the United States. The edited volume presents a holistic and multidisciplinary perspective of this group, and it critically documents how Latinas and Latinos have changed andwill continue to change the face of América.